(3GdJjSjQ aj GdJaSjQs - (3eMeO Hf QVj GdOjf eMeO Hf eMeO GdZqRj GdYGeQj GdTGaYj , HOQ GdOjf , J (B984 (3g`s ((3jMji Hf eMeO s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jS hGdbQBf GdMcje Efc def GdoeQSdjf Yf GdfHi GdoeUWai JSei HbdH GdbQBf s
(3BNQgG (B:s
(3Ydi JeGe fYeI GdESdGe hcd eG CJe ef CfYGe Ke GdUdGg hGdSdGe hcGf GdaQGZ ef fSNI s
(3GdfSNI HgG MhGTs
(3fXe s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs